Osteogenesis imperfecta and primary open angle glaucoma: Genotypic analysis of a new phenotypic association - Wallace, Dana J. (Molecular Vision, 2014)
PURPOSE: Osteogenesis imperfecta (OI) is a group of inherited disorders characterized by bone fragility. Ocular findings include blue sclera, low ocular rigidity, and thin corneal thickness. However, there are no documented cases linking OI and primary open angle glaucoma (POAG). In this report, we describe three individuals, one isolated case and two from a multiplex family, with OI type I and POAG. METHODS: Available family members with OI and POAG had a complete eye examination, including visual acuity, intraocular pressure (IOP), pachymetry, slit-lamp exam, dilated fundus exam, and visual fields. DNA from blood samples was sequenced and screened for mutations in COL1A1/2 and myocilin (MYOC). RESULTS: All subjects had OI type I. Findings of POAG included elevated IOP, normal gonioscopy, and glaucomatous optic disc cupping and visual field loss. POAG cosegregated with OI in the multiplex family. The multiplex family had a single nucleotide insertion (c.540_541insC) in COL1A1 resulting in a frameshift mutation and a premature termination codon. The sporadic case had a COL1A1 splice acceptor site mutation (c.2452–2A>T or IVS36–2A>T) predicted to result in a premature termination codon due to intron inclusion or a cryptic splice site. None of the glaucoma cases had mutations or sequence changes in MYOC. CONCLUSIONS: We identified two novel mutations in COL1A1 in individuals with OI type I and POAG. Thus, some mutations in COL1A1 may be causative for OI and POAG. Alternatively, susceptibility genes may interact with mutations in COL1A1 to cause POAG.